From Data to Illustrations: Common (Free) Tools for Proper Image Data Handling and Processing - Cvrčková, Fatima (Methods in molecular biology (Clifton, N.J.), 2019)
Studying morphogenesis is unthinkable without visualizing shapes, and sharing the results of such studies critically depends on communicating image data. Despite a wealth of literature dealing with acquisition and analysis of image data, visualizing them for publication or presentation purposes remains a craft learned mainly by experience. This chapter provides a practical guide to producing publication-grade illustrations out of raw microscopic (or other) digital images, using mostly or exclusively free software, and points out some common problems and their solutions.
Keywords: Computers; Vector; Inkscape; Bitmap; počítače; Data visualization; Microscopy; Image Processing, Computer-Assisted; Software; počítačové zpracování obrazu; Computer graphics; mikroskopie; ImageJ; Raster; Resolution; software; Bit depth; Computer Graphics; počítačová grafika